Екинши жер жүзлик урыс жыллары қарақалпақстан баспасында жазыўшы шайырларының дөретпелери - Қабулова, М.Т (SCIENCE and SOCIETY, 2022)
The article reveals the images of Karakalpak writers during the Second World War. It is written about the collections of writers' war- motivated works published during the war. The newspaper "Kyzyl Karakalpakstan" also reported that it played a significant role in
Keywords: journalism; research; publicism; press; era; poet